2019
DOI: 10.1039/c8ce02072h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the physico-chemical properties of BiOBr via solvent adjustment: towards an efficient photocatalyst for water treatment

Abstract: BiOBr with a nanosheet structure and exposed (001) surface was prepared by a facile one-pot solvothermal approach in benzyl alcohol solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It is widely accepted that the crystal structure, specific surface area, separation efficiency of photogenerated electron–hole pairs and exposed facets play an important role in the photocatalytic reaction [ 48 , 49 , 50 ]: the suitable heterostructure, the larger specific surface area, the higher separation efficiency of photogenerated electron–hole pairs, and the higher reactive exposed facet are conductive to the improvement of the photocatalytic activity. A possible photocatalytic mechanism of TiO 2 /CdS heterostructure for the photodegradation of MO under ultraviolet light irradiation is shown in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that the crystal structure, specific surface area, separation efficiency of photogenerated electron–hole pairs and exposed facets play an important role in the photocatalytic reaction [ 48 , 49 , 50 ]: the suitable heterostructure, the larger specific surface area, the higher separation efficiency of photogenerated electron–hole pairs, and the higher reactive exposed facet are conductive to the improvement of the photocatalytic activity. A possible photocatalytic mechanism of TiO 2 /CdS heterostructure for the photodegradation of MO under ultraviolet light irradiation is shown in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…When used for photodegradation of reactive brilliant blue (KN-R), flower-like BiOBr prepared in glycerin presented the highest activity for the small size, exposed active face and abundant oxygen vacancies. Wei et al 30 synthesized several BiOBr photocatalysts by using ethanol, ethylene glycol, tert -butanol, benzyl alcohol, and 2-methoxyethanol solvent. As a result, thin BiOBr nanosheets synthesized in benzyl alcohol presented the outstanding photocatalytic activity for degradation of Rh B, due to the exposed (001) facets.…”
Section: Controllable Synthesis Of Bioxmentioning
confidence: 99%
“…It is found that semiconductor photocatalysis can replace the abovementioned traditional methods. The dyes in dyestuff wastewater can be decomposed into small organic molecules and eventually mineralized into H 2 O, CO 2 , and other inorganic ions under the irradiation of visible or ultraviolet light because of its high catalytic performance, nonselective oxidation, nontoxicity, low expenses, and secondary pollution. Therefore, it is very important to design and synthesize novel photocatalysts with high catalytic activity to solve the problem of highly polluted textile wastewater. In a variety of semiconductor photocatalysts, titanium dioxide (TiO 2 ) is considered to be the most widely used catalyst for the photocatalytic degradation of organic pollutants because of its outstanding chemical and thermal stability, great oxidizing power, excellent photochemical activity, harmlessness, and nontoxicity. Among the four confirmed polymorphs of TiO 2 (anatase, rutile, brookite, and TiO 2 -B), the anatase phase has been widely regarded to exhibit the most photoactive reactivity in photocatalysis applications, which can be attributed to the lower rate of charge recombination and the stronger interaction between the organic molecules and the anatase surfaces. , However, the rapid recombination rate of photogenerated electrons and holes leads to a reduction in quantum efficiency and limits the photocatalytic ability of anatase .…”
Section: Introductionmentioning
confidence: 99%